Pendidikan Kesehatan Melalui Penyuluhan Dampak Mengkonsumsi Mi Instan Secara Berlebihan Bagi Mahasiswa Program Studi Sarjana Gizi Stikes Persada Nabire - Kanang, Bau; Pamerlia R Rumkorem; Olince Nawipa; Agustina Madai; Jemi Mote; Obet Nego (JCS, 2024)
Health education is carried out to change people's wrong behavior in the field of nutrition so that healthy people can be created with normal nutrition and protected from degenerative diseases. Behavior related to efforts to maintain and improve health. One healthy behavior is eating a balanced menu. However, Indonesia is in second place as the country that consumes the most instant noodles in the world in 2022, 14.26 billion portions. This number accounts for 11.76% of world instant noodle consumption. There are several impacts of instant noodles on health such as digestive disorders, kidney disorders, obesity, hypertension and metabolic syndrome. The aim of this activity is to increase knowledge of the impacts of consuming too much instant noodles. This activity uses preparation, implementation and evaluation methods, the activity is carried out in the Nutrition laboratory at the STIKes Persada Nabire Campus, Central Papua Province in June 2024. The results of this activity have a positive impact because it increases knowledge and adds insight to achieve optimal health and change behavior. eating instant noodle food often will become occasional. Getting used to eating healthy, nutritious and protein-rich foods. Consuming instant noodles healthily requires knowing how to process them properly.